Triple Oxygen Isotope Measurements (Δ'17O) of Body Water Reflect Water Intake, Metabolism, and δ18O of Ingested Water in Passerines - Sabat, Pablo; Newsome, Seth D.; Pinochet, Stephanie; Nespolo, Roberto; Sanchez-Hernandez, Juan Carlos; Maldonado, Karin; Gerson, Alexander R.; Sharp, Zachary D.; Whiteman, John P. (Frontiers in Physiology, 2021)
Abstract Understanding physiological traits and ecological conditions that influence a species reliance on metabolic water is critical to creating accurate physiological models that can assess their ability to adapt to environmental perturbations (e.g., drought) that impact water availability. However, relatively few studies have examined variation in the sources of water animals use to maintain water balance, and even fewer have focused on the role of metabolic water. A key reason is methodological limitations. Here we applied a new method that measures the triple oxygen isotopic composition of a single blood sample to estimate the contribution of metabolic water to the body water pool of three passerine species. This approach relies on Δ'17O, defined as the residual from the tight linear correlation that naturally exists between δ17O and δ18O values. Importantly, Δ'17O is relatively insensitive to key fractionation processes such as Rayleigh distillation in the water cycle that have hindered previous isotope-based assessments of animal water balance. We evaluated the effects of changes in metabolic rate and water intake on Δ'17O values of captive rufous-collared sparrows (Zonotrichia capensis) and two invertivorous passerine species in the genus Cinclodes from the field. As predicted, colder acclimation temperatures induced increases in metabolic rate, decreases in water intake, and increases in the contribution of metabolic water to the body water pool of Z. capensis, causing a consistent change in Δ'17O. Measurement of Δ'17O also provides an estimate of the δ18O composition of ingested preformed (drinking/food) water. Estimated δ18O values of drinking/food water for captive Z. capensis was ~ -11‰, which is consistent with that of tap water in Santiago, Chile. In contrast, δ18O values of drinking/food water ingested by wild-caught Cinclodes was similar to that of seawater, which is consistent with their reliance on marine resources. Our results confirm the utility of this method for quantifying the relative contribution of metabolic versus preformed drinking/food water to the body water pool in birds.